2013
DOI: 10.4177/ccgp-d-12-00011.1
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical Characterization of Clinker-Stabilized Fly Ash - Coal Mine Overburden Mixes for Subbase of Mine Haul Road

Abstract: A B S T R A C TFly ash is a major by-product of thermal power plants that adversely affects land, water, and air. Its gainful utilization in many areas is being continuously explored. Use of fly ash in opencast coal mine haul road construction is one such option. This article reports detailed laboratory investigations carried out on clinker-stabilized fly ash-mine overburden mixes to evaluate their suitability for subbase of mine haul roads. Composite materials were prepared from fly ash, mine overburden, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Rajak et al [59] reported that UCS value get increased by 9.34% with the addition of 20% fly ash in OB material. Few additives were added in different proportions with the fly ash-OB mix like lime [63,64,70], clinker [71,72], cement [68], GGBS [56], and kiln dust [69] to determine the UCS value. The best suitable results of UCS value under different mix proportions of OB material, fly ash, or/and additive are described in the Table 4.…”
Section: Unconfined Compressive Strength (Ucs) Valuementioning
confidence: 99%
“…Rajak et al [59] reported that UCS value get increased by 9.34% with the addition of 20% fly ash in OB material. Few additives were added in different proportions with the fly ash-OB mix like lime [63,64,70], clinker [71,72], cement [68], GGBS [56], and kiln dust [69] to determine the UCS value. The best suitable results of UCS value under different mix proportions of OB material, fly ash, or/and additive are described in the Table 4.…”
Section: Unconfined Compressive Strength (Ucs) Valuementioning
confidence: 99%